Autoimmune Haemolytic Anaemia in Pregnancy: A Case Report With Literature Review (Journal of Chittagong Medical College Teachers' Association, 2019)
Autoimmune Haemolytic Anaemia (AIHA) results from increased red cell destruction due to red cell autoantibodies. Pregnancy associated AIHA is a very rare condition with unexplained entity, but can be dangerous for both fetus and mother. A case of multipara lady who developed haemolyticanamia during pregnancy, with a wide range of differential diagnosis. She was responded well to moderate dose of steroid with good feto-maternal outcome. Autoimmune haemolytic anaemia in pregnancy has rarely been reported in literature, which deserve its presentation.JCMCTA 2019 ; 30 (1) : 61-63